Holocene vegetation and fire dynamics in the supra-mediterranean belt of the Nebrodi Mountains (Sicily, Italy) - Bisculm, Martina; Colombaroli, Daniele; Vescovi, Elisa; van Leeuwen, Jacqueline F. N.; Henne, Paul D.; Rothen, Julian; Procacci, Giovanni; Pasta, Salvatore; La Mantia, Tommaso; Tinner, Willy (Journal of Quaternary Science, 2012)
High-resolution pollen, macrofossil and charcoal data, combined with accelerator mass spectrometry 14C dating and multivariate analysis, were used to reconstruct Holocene vegetation and fire dynamics at Urio Quattrocchi, a small lake in the supra-mediterranean belt in the Nebrodi Mountains of Sicily (Italy). The data suggest that after 10 000 cal a BP increasing moisture availability supported closed forests with deciduous (Quercus cerris, Fagus sylvatica and Fraxinus spp.) and evergreen (Quercus ilex) species. Species-rich closed forest persisted until 6850 cal a BP, when Neolithic activities caused a forest decline and affected plant diversity. Secondary forest with abundant Ilex aquifolium recovered between 6650 and 6000 cal a BP, indicating moist conditions. From 5000 cal a BP, agriculture and pastoralism led to the currently fragmented landscape with sparse deciduous forests (Quercus cerris). The study suggests that evergreen broadleaved species were more important at elevations above 1000 m a.s.l. before ca. 5000 cal a BP than subsequently, which might reflect less human impact or warmer-than-today climatic conditions between 10 000 and 5000 cal a BP. Despite land use since Neolithic times, deciduous supra-mediterranean forests were never completely displaced from the Nebrodi Mountains, because of favourable moist conditions that persisted throughout the Holocene. Reconstructed vegetation dynamics document the absence of any pronounced mid- or late-Holocene ‘aridification’ trend at the site, an issue which is controversially debated in Italy and the Mediterranean region. Copyright © 2012 John Wiley & Sons, Ltd.
The following values have no corresponding Zotero field: publisher: John Wiley & Sons, Ltd.
Keywords: climate change; human impact; Ilex aquifolium; macrofossils; pollen; Quercus ilex